Упавшие в зону. Вынужденная посадка - Буторин Андрей Русланович (S.T.A.L.K.E.R, 2015)
Экземпляры: ф 13 (20151116) / Инвентарный номер: 191118 / Цена: 251.75 / Сис.шифр: 84(2Рос=Рус)6-44 / Авт.знак: Б 93 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6-44